Parenting styles and obsessive-compulsive symptoms in college students: the mediating role of perfectionism - Po Hu; Pengwei Liang; Xiaoyan Liu; Yuting Ouyang; Jianping Wang (Frontiers in Psychiatry, 2023)
IntroductionObsessive-compulsive symptoms is a common psychological phenomenon among early adulthood college students, which are closely related to their parents’ parenting styles. Theoretical and some empirical studies have suggested the mediating role of perfectionism in this process, but this has not been confirmed, and the binary perspective of positive-negative perfectionism has not been addressed in this issue.MethodsThis study aimed to investigate the mediating role of perfectionism in the relationship between parenting styles and obsessive-compulsive symptoms among college students. A total of 661 college students participated in this study.ResultsNegative perfectionism mediated the relationship between negative parenting style and obsessive-compulsive symptoms among college students. Negative parenting style predicted obsessive-compulsive symptoms through its positive predictive effect on negative perfectionism. However, the mediating effect of positive perfectionism was not significant in this process.DiscussionThis study provides further evidence of the mechanisms underlying the occurrence of obsessive-compulsive symptoms, and offers new ideas for interventions for OCD.